2019
DOI: 10.1002/ett.3799
|View full text |Cite
|
Sign up to set email alerts
|

Oblique projection: An interference mitigation for MIMO multihop full‐duplex relay

Abstract: Full-duplex (FD) assisted multiple-input-multiple-output relaying increases the spectral efficiency through efficient spectrum utilization. The major concerns for the FD assisted relay system are the cancellation of inter-relay interference (IRI) and relay self-interference (RSI). Previous works were idealized only on the basis of either RSI or IRI; hence, all other realistic models to overcome the RSI or IRI were unappreciated. This paper aims to reduce the interference-to-signal ratio. We propose the joint r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…The proof is concluded. APPENDIX B PROOF OF (12), (13), AND (14) By substituting (3) into (11), the average BLER at hop k for TAS/MRC is calculated as into (B.1), we obtain (12). The derivations of ( 13) and ( 14) can be demonstrated by using the same methods as those in (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proof is concluded. APPENDIX B PROOF OF (12), (13), AND (14) By substituting (3) into (11), the average BLER at hop k for TAS/MRC is calculated as into (B.1), we obtain (12). The derivations of ( 13) and ( 14) can be demonstrated by using the same methods as those in (12).…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that distributing the interference rejection capability between both terminals performed better than letting either the transmitter or receiver remove the SLI and crosstalk interference. In [12], Madani et al proposed a joint-relay receive beamforming technique on oblique projections to mitigate residual SLI and inter-relay interference in multihop MIMO FDR environments. The results claimed that (i) the proposed methodology could be adopted, even when the residual SLI and inter-relay interference channels were unavailable; and (ii) the signal-to-interference-plus-noise ratio (SINR) would not deteriorate, even in the high transmit-power regime.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers worked on the mitigation of both interferences related to relay, i.e., IRI and RSI. Subsequently, in [136], authors investigated RSI and IRI for FDR. They are using oblique projection and orthogonal projector techniques to nullify relays interferences.…”
Section: ) Inter-relay Interferencementioning
confidence: 99%
“…The results revealed that distributing the interference rejection capability between both terminals performed better than letting either the transmitter or receiver remove the SLI and crosstalk interference. In [11], Madani et al proposed a joint-relay receive beamforming technique on oblique projections to mitigate residual SLI and inter-relay interference in multihop MIMO FDR environments. The results claimed that (i) the proposed methodology could be adopted, even when the residual SLI and inter-relay interference channels were unavailable; and (ii) the signal-tointerference-plus-noise ratio (SINR) would not deteriorate, even in the high transmit-power regime.…”
Section: Introductionmentioning
confidence: 99%